Do Large-Scale Student Assessments Really Capture Cognitive Skills? - de Hoyos, Rafael (World Bank, Washington, DC, 2021)
This paper studies the relationship between test scores and cognitive skills using two longitudinal data sets that track student performance on a national standardized exam in grades 6, 9, and 12 and post-secondary school outcomes in Mexico. Using a large sample of twins, the analysis finds that primary school test scores are a strong predictor of secondary education outcomes and that this association is mainly driven by the relationship between test scores and cognitive skills, as opposed to family background and other general skills. Using a data set that links results in the national standardized test to later outcomes, the paper finds that secondary school test scores predict university enrollment and hourly wages. These results indicate that, despite their limitations, large-scale student assessments can capture the skills they are meant to measure and can therefore be used to monitor learning in education systems.